Food Hygiene Practices and Associated Factors Among Food Handlers Working in Food Establishments in the Bole Sub City, Addis Ababa, Ethiopia - Abdi AM; Amano A; Abrahim A; Getahun M; Ababor S; Kumie A (Dove Medical Press, 2020)
Ahmed Mohammed Abdi,1 Abdella Amano,2 Abadir Abrahim,3 Mulusew Getahun,4 Sabit Ababor,5 Abera Kumie6 1Department of Public Health Emergency Management, Ethiopian Public Health Institute, Gulele Sub City, Addis Ababa, Ethiopia; 2Department of Public Health, Hawassa University, Hawassa, SNNPR, Ethiopia; 3Department of Business Administration, Jimma University, Jimma, Oromia Regional State, Ethiopia; 4Department of Immunology and Hematology, Ethiopian Public Health Institute, Gulele Sub City, Addis Ababa, Ethiopia; 5Department of Public Health, Ethiopian Public Health Institute, Gulele Sub City, Addis Ababa, Ethiopia; 6Department of Preventive Medicine, Addis Ababa University, Lideta Sub City, Addis Ababa, EthiopiaCorrespondence: Ahmed Mohammed AbdiDepartment of Public Health Emergency Management, Ethiopian Public Health Institute, P.O. Box 102249, Gulele Sub City, Addis Ababa, EthiopiaTel +251911910058Email ahmee60@yahoo.comBackground: Consumers’ health would be at risk unless food preparation and handling hygiene is ensured by food establishments. Literature indicates that poor food handling and sanitation practices are more common among food handlers in developing countries resulting in food-borne illness. Hence, food handlers can play a significant role in ensuring food hygiene. To this end, the paper aims to assess the level of food hygiene practices and its associated factors of food handlers working in food establishments in Bole sub-city, Addis Ababa, Ethiopia.Methods: Through across-sectional study design, a total of 394 food handlers selected randomly from food establishments have participated in the study. The data were collected between July and December 2017, through interview and observation. Percentage, cross tabulations, and logistic regressions were used to analyze the data.Results: The findings show that among 394 study subjects only 27.4% (i.e., 108 food handlers), were found to have good food hygiene practices. In other words, majority of food handlers observed were poor in maintaining food hygiene. Food hygiene practices were highly influenced by level score of favorable attitude (AOR = 3.9, 95% CI = 1.93, 7.87), extensive knowledge towards food hygiene (AOR= 3.33, 95% CI= 1.93, 5.76) and availability of water storage equipment at food establishments (AOR= 2.67, 95% CI= 1.38, 5.15).Conclusion: Food handlers had poor food hygiene practices in the study area. Shortages of a continuous water supply at food establishments, poor knowledge, and unfavorable attitude of food handlers towards food hygiene practice were all contributing factors associated with poor food hygiene practice. However, these can be improved through health education programs and environmental health services, such as periodic inspections, effective enforcement of food safety regulations, and enhancing the capacity of food hygiene regulators.Keywords: food hygiene, food handlers, Addis Ababa Ethiopia